Formyl Peptide Receptor 2 Plays a Deleterious Role During Influenza A Virus Infections. (30th March 2016) - Tcherniuk, Sergey; Cenac, Nicolas; Comte, Marjorie; Frouard, Julie; Errazuriz-Cerda, Elisabeth; Galabov, Angel; Morange, Pierre-Emmanuel; Vergnolle, Nathalie; Si-Tahar, Mustapha; Alessi, Marie-Christine; Riteau, Béatrice
Abstract: Background. The pathogenesis of influenza A virus (IAV) infections is a multifactorial process that includes the replication capacity of the virus and a harmful inflammatory response to infection. Formyl peptide receptor 2 (FPR2) emerges as a central receptor in inflammatory processes controlling resolution of acute inflammation. Its role in virus pathogenesis has not been investigated yet. Methods. We used pharmacologic approaches to investigate the role of FPR2 during IAV infection in vitro and in vivo. Results. In vitro, FPR2 expressed on A549 cells was activated by IAV, which harbors its ligand, annexin A1, in its envelope. FPR2 activation by IAV promoted viral replication through an extracellular-regulated kinase (ERK)–dependent pathway. In vivo, activating FPR2 by administering the agonist WKYMVm-NH2 decreased survival and increased viral replication and inflammation after IAV infection. This effect was abolished by treating the mice with U0126, a specific ERK pathway inhibitor, showing that, in vivo, the deleterious role of FPR2 also occurs through an ERK-dependent pathway. In contrast, administration of the FPR2 antagonist WRW4 protected mice from lethal IAV infections. Conclusions. These data show that viral replication and IAV pathogenesis depend on FPR2 signaling and suggest that FPR2 may be a promising novel strategy to treat influenza.